Depression and use of antidepressants among undergraduate medical students (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: Depression is one of the most prevalent conditions worldwide. Medical students are known to be the victims of tremendous stress. The objective of this study was to assess the prevalence of depression and the use of antidepressants among undergraduate medical students.Materials and Methods: A descriptive cross-sectional questionnaire based study was carried out among the undergraduate basic science medical students of first and second year of Janaki Medical College, Janakpurdham, from May 2021 to September 2021. Depression levels were assessed using Zung Depression Scale.Results: Among 111 students 22% were depressed, 17.7% were depressed among first year students while 26.5% were depressed among second year students. 23.9% males and 17.5% females were depressed while only 5.4% were on antidepressant drugs. Both year students gave higher ratings to academic stress and financial problems as stressors.Conclusion: The prevalence of depression was higher, seen especially in second year students. Therefore, there is a need for counseling services to them.